Antibiotic susceptibility profiles and genotypic characteristics of tetracycline–resistant Streptococcus pyogenes isolated from hospitals in Malaysia - Abd. Ulatif, Aya Muktar (2017)
Streptococcus pyogenes(group A streptococcus) is one of the most prevailing human pathogens causing a wide variety of infectious diseases and immunological complications. Tetracyclines are one of the alternative drugs used for its therapy. However, there is an increasing evidence of resistance and clinical failures towards these drugs reported globally. This condition is now becoming a great concern as tetracycline resistance genes can be easily transferred via horizontal gene transfer as well as the spread of clonal strains. Moreover, certain emm types and clones are said to be associated with particular diseases. The aims of this study were to determine antibiotic susceptibility profiles and genotypic characteristics of tetracycline resistance among S. pyogenes isolates as well as to identify the M-protein by means of emm-typing. A total of 42 S. pyogenes clinical isolates were obtained from Kuala Lumpur and Serdang hospitals. Phenotypic detection methods were carried out by using Gram-stain, colony morphology on Blood agar, bacitracin and PYR tests. Antibiotic susceptibility testing was done by disc-diffusion method and interpreted according to CLSI guideline. Minimum inhibitory concentration of tetracycline-resistant isolates were conducted by E-test method and interpreted according to CLSI guideline. Tetracycline resistance genes were detected by PCR using established primers. emm typing was established by sequencing the PCR products. All isolates were susceptible to penicillin, erythromycin and linezolid. Thirty isolates (71.4%) were resistant to tetracyclines which comprised tetracycline, minocycline, and doxycycline. Of 30 tetracycline-resistant strains, 73.3% of isolates harboured tet(M) gene alone while 10%, 10% and 3.3% had a combination of tet(M)/tet(L), tet(M)/tet(O)/tet(L) and tet(M)/tet(O) genes, respectively. No tetracycline genes were detected in one resistant isolate (3.3%). GAS from non-invasive specimens exhibited higher number of tetracycline-resistant isolates compared to invasive specimens (42.8% versus 28.5%). A total of 25 different emm types were detected The most frequent emm types identified were emm63 (9.5%) followed by 7.1% of emm18.21, emm28.5, emm1.0, emm89 and emm91. No new emm types were detected. Eighteen emm types (72%) were tetracycline resistance strains and emm63 (13.3%) was frequently described among them.emm18.21 type (3 isolates) was the most frequently described among invasive isolates. High number of tetracycline-resistant GAS and its tetracycline genes in the present study possesses a great risk of impending outbreaks in hospital and community settings. Antibiotic surveillance system and antibiotic stewardship program should be continuously maintained to overcome this problem in future. High genetic diversity of emm types would hinder the development of suitable vaccine candidates. However, a multicentre study is warranted to establish the potential vaccine coverage for our local population.